Neuronal Sigma-1 Receptors: Signaling Functions and Protective Roles in Neurodegenerative Diseases - Ryskamp, Daniel A.; Korban, Svetlana; Zhemkov, Vladimir; Kraskovskaya, Nina; Bezprozvanny, Ilya (Frontiers in Neuroscience, 2019)
Sigma-1 receptor (S1R) is a multi-functional, ligand-operated protein situated in endoplasmic reticulum (ER) membranes and changes in its function and/or expression have been associated with various neurological disorders including amyotrophic lateral sclerosis/frontotemporal dementia, Alzheimer’s (AD) and Huntington’s diseases (HD). S1R agonists are broadly neuroprotective and this is achieved through a diversity of S1R-mediated signaling functions that are generally pro-survival and anti-apoptotic; yet, relatively little is known regarding the exact mechanisms of receptor functioning at the molecular level. This review summarizes therapeutically relevant mechanisms by which S1R modulates neurophysiology and implements neuroprotective functions in neurodegenerative diseases. These mechanisms are diverse due to the fact that S1R can bind to and modulate a large range of client proteins, including many ion channels in both the ER and the plasma membrane. We summarize the effect of S1R on its interaction partners and consider some of the cell type- and disease-specific aspects of these actions. Besides direct protein interactions in the endoplasmic reticulum, S1R is likely to function at the cellular/interorganellar level by altering the activity of several plasmalemmal ion channels through control of trafficking, which may help to reduce excitotoxicity. Moreover, S1R is situated in lipid rafts where it binds cholesterol and regulates lipid and protein trafficking and calcium flux at the mitochondrial associated membrane (MAM) domain. This may have important implications for MAM stability and function in neurodegenerative diseases as well as cellular bioenergetics. We also summarize the structural and biochemical features of S1R proposed to underlie its activity. In conclusion, S1R is incredibly versatile in its ability to foster neuronal homeostasis in the context of several neurodegenerative disorders.